2008
DOI: 10.1108/14676370810885853
|View full text |Cite
|
Sign up to set email alerts
|

An overview of extra‐curricular education for sustainable development (ESD) interventions in UK universities

Abstract: PurposeThe purpose of this paper is to explore the extent and type of extra‐curricular ESD‐related practice in UK universities and to record opinions about the utility of such work.Design/methodology/approachA postal questionnaire survey of all UK universities was undertaken in 2006. Over half (51 per cent) of the UK's 140 universities with degree‐awarding powers responded.FindingsExtra‐curricular ESD‐related interventions were found to be widespread and in 31 per cent of cases were the primary approach to ESD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 10 publications
0
19
0
3
Order By: Relevance
“…In research on the South Pacific Island Nations, it has been found that sustainability tended to be integrated into all curricula in PSE [26]. A cross-institutional study from 2008 also found that integration of sustainability principles is on the increase across a wide range of extra-curricular activities in a number of PSE institutions within the UK [27]. With these exceptions, studies comparing approaches to sustainability in the curriculum across different disciplines were found to be rare in our analysis.…”
Section: Curriculamentioning
confidence: 54%
“…In research on the South Pacific Island Nations, it has been found that sustainability tended to be integrated into all curricula in PSE [26]. A cross-institutional study from 2008 also found that integration of sustainability principles is on the increase across a wide range of extra-curricular activities in a number of PSE institutions within the UK [27]. With these exceptions, studies comparing approaches to sustainability in the curriculum across different disciplines were found to be rare in our analysis.…”
Section: Curriculamentioning
confidence: 54%
“…Empirical literature across the globe has explored education as a means for sustainability. [5][6][7][8][9][10][11][12][13] Environmental education is one of the most successful and effective methods to disseminate and influence behaviors, values and knowledge in society. [14][15][16][17][18][19][20][21][22][23][24][25] Bekessy 26 and Holdsworth 27 investigated the level of sustainability advancement at various university levels in Australia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A importância das atividades realizadas pelos programas de educação ambiental em instituições de ensino superior pode ainda ser demonstrada pelo levantamento realizado por Lipscomb et al (2008) em universidades do Reino Unido. Os resultados demonstraram que intervenções extracurriculares têm impacto maior sobre as atitudes das pessoas que disciplinas e projetos curriculares.…”
Section: Introductionunclassified
“…Os resultados demonstraram que intervenções extracurriculares têm impacto maior sobre as atitudes das pessoas que disciplinas e projetos curriculares. No entanto, esse tipo de intervenção tem sido pouco explorado por essas instituições; a constatação é que pouco recurso, tempo e dinheiro é dedicado a essas atividades (FERRER-BALAS et al, 2008;LIPSCOMB et al, 2008).…”
Section: Introductionunclassified